2010
DOI: 10.1370/afm.1121
|View full text |Cite
|
Sign up to set email alerts
|

Patient Outcomes at 26 Months in the Patient-Centered Medical Home National Demonstration Project

Abstract: After slightly more than 2 years, implementation of PCMH components, whether by facilitation or practice self-direction, was associated with small improvements in condition-specific quality of care but not patient experience. PCMH models that call for practice change without altering the broader delivery system may not achieve their intended results, at least in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
175
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(176 citation statements)
references
References 31 publications
1
175
0
Order By: Relevance
“…15,16 A greater understanding is needed of the organizational factors influencing a practice's degree of PCMH adoption, including the awareness and commitment not only of practice leadership and primary care providers, but of all employees. [17][18][19] A second potential reason for the lack of perception among respondents of structural changes intended to benefit them is the targeted population. Although practices have adopted PCMH standards uniformly for all patients, for our study, we chose to focus on patients that had at least one chronic condition, namely, diabetes and/or hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 A greater understanding is needed of the organizational factors influencing a practice's degree of PCMH adoption, including the awareness and commitment not only of practice leadership and primary care providers, but of all employees. [17][18][19] A second potential reason for the lack of perception among respondents of structural changes intended to benefit them is the targeted population. Although practices have adopted PCMH standards uniformly for all patients, for our study, we chose to focus on patients that had at least one chronic condition, namely, diabetes and/or hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of 8 published studies found a small, positive effect of PCMH recognition on patient experience; however, only 3 studies included children, 3 and 1 of those found no effect on patient experience. 9 Therefore, results are mixed, and more research on child patient experiences is needed to inform the next steps in the transformation of health care systems.…”
mentioning
confidence: 99%
“…5,6 Despite the emphasis placed on comprehensiveness, patient-centeredness, and extended access in prevailing health care redesign efforts, how these attributes influence utilization of preventive services at the national level is little studied. Existing research consists of ecological studies, 7 small pilot projects, 8 and larger comparative studies. 9,10 However, nearly all have been limited to a relatively narrow group of patients (eg, those with certain chronic diseases, geriatric patients, pediatric patients) and/or to a single geographic site (eg, managed care organizations, hospital regions, single primary care practices).…”
mentioning
confidence: 99%